Properties of L-type calcium channel gating current in isolated guinea pig ventricular myocytes (The Rockefeller University Press, 1991)
Nonlinear capacitative current (charge movement) was compared to the Ca current (ICa) in single guinea pig ventricular myocytes. It was concluded that the charge movement seen with depolarizing test steps from -50 mV is dominated by L-type Ca channel gating current, because of the following observations. (a) Ca channel inactivation and the immobilization of the gating current had similar voltage and time dependencies. The degree of channel inactivation was directly proportional to the amount of charge immobilization, unlike what has been reported for Na channels. (b) The degree of Ca channel activation was closely correlated with the amount of charge moved at all test potentials between -40 and +60 mV. (c) D600 was found to reduce the gating current in a voltage- and use-dependent manner. D600 was also found to induce "extra" charge movement at negative potentials. (d) Nitrendipine reduced the gating current in a voltage-dependent manner (KD = 200 nM at -40 mV). However, nitrendipine did not increase charge movement at negative test potentials. Although contamination of the Ca channel gating current from other sources cannot be fully excluded, it was not evident in the data and would appear to be small. However, it was noted that the amount of Ca channel gating charge was quite large compared with the magnitude of the Ca current. Indeed, the gating current was found to be a significant contaminant (19 +/- 7%) of the Ca tail currents in these cells. In addition, it was found that Ca channel rundown did not diminish the gating current. These results suggest that Ca channels can be "inactivated" by means that do not affect the voltage sensor.